Reducing anxiety symptoms in adolescents with pre-existing depression: results from a randomized control trial - Solberg, Henriette; Idsoe, Thormod; Keles, Serap (Frontiers in Psychiatry, 2025)
IntroductionDepression and anxiety have a long history of co-occurrence, with a relatively high prevalence in the Norwegian population both separate and combined. In adolescence, this prevalence increases significantly and may impact youths’ social and academic functioning drastically. Having effective treatments aimed at adolescents may have potential to prevent both short and long-term effects associated with these disorders. The aim of the current study was to examine whether the “Adolescent Coping with Depression Course” (ACDC), a cognitive behaviour therapy (CBT)-based group intervention aimed at adolescents with subclinical mild-to-moderate depressive symptoms, would also be effective in reducing anxiety symptoms.MethodsData, which came from a two-arm parallel cluster randomised control trial conducted in Norway, were collected from 228 adolescents, 133 of whom were assigned to the 14-week ACDC intervention and 95 were assigned to the usual care condition. The data were analysed with structural equation modellingResultsThe results indicated that the intervention is effective in reducing anxiety symptoms via reducing the depressive symptoms, thus illustrating an indirect effect.DiscussionThe findings suggested that ACDC has the potential to reduce anxiety symptoms over time through its effect on depressive symptoms. Implications of the results are presented.Clinical trial registrationhttps://www.isrctn.com, identifier ISRCTN19700389.